Hajj Resilience in Crisis: Analysis of Fairclough's Critical Discourse from Detik.Com's 2026 Hajj Coverage - Ahmad Kamalul Fikri; Mohammad Andi Hakim (International Tatho Academics, 2026)
This article examines how Detik.com discursively constructed Hajj 2026 amid escalating Middle Eastern tensions involving Iran, the United States, and Israel. While previous Indonesian applications of Fairclough’s Critical Discourse Analysis have largely focused on electoral politics, religious moderation, and domestic ideological contestation, limited attention has been given to how online news frames pilgrimage resilience during geopolitical crisis. Using Norman Fairclough’s three-dimensional CDA, this study analyzes ten Detik.com reports published between March and April 2026. The analysis focuses on textual strategies, discursive production, and sociocultural explanation. The findings show that Detik.com systematically framed Hajj as safe, continuous, and spiritually protected through repetitive reassurance, dominant reliance on official voices, and narratives of economic shielding. At the textual level, the reports privilege certainty, continuity, and calm; at the discursive level, they circulate an official reassurance frame across multiple channels; and at the sociocultural level, they prioritize spiritual stability and state legitimacy over geopolitical anxiety. This article offers a conceptual contribution through the notion of hajj resilience discourse, defined as a mediated formation in which language, authority, and religious symbolism jointly sustain trust in worship under crisis conditions.